HIGH SPEED UNIVERSAL HASHING BASED ON MANY STREAM COMPUTING - Котух, Євген Володимирович; Карташов, Володимир Михайлович; Цапко, Денис Петрович; Халімов, Олег Геннадійович; Самойлова, Аліна Вадимівна (Ukrainian Information Security Research Journal, 2015)
Universal hashing determines provably resistantauthentication with the meter, provides high resistance tocollisions and computing speed. One of the mostpromising areas in addressing the challenges of highspeedcomputing is the use of technology GPGPU(General-purpose graphics processing units). GPGPUtechnology enables one solver to achieve a high level ofparallelism without the time-consuming data transfer andsynchronization between the nodes of the calculationresults. To enhance the universal hash-based scalarpolynomial computations and developed proposals for alot of stream computing, calculations in modulararithmetic and arithmetic over the extended finite fieldwith GPGPU technology.